2022
DOI: 10.1002/adma.202202685
|View full text |Cite
|
Sign up to set email alerts
|

Highly Potassiophilic Graphdiyne Skeletons Decorated with Cu Quantum Dots Enable Dendrite‐Free Potassium‐Metal Anodes

Abstract: Employing an Al foil current collector at the potassium anode side is an ideal choice to entail low‐cost and high‐energy potassium‐metal batteries (PMBs). Nevertheless, the poor affinity between the potassium and the planar Al can cause uneven K plating/stripping and, hence, an undermined anode performance, which remains a significant challenge to be addressed. Herein, a nitrogen‐doped carbon@graphdiyne (NC@GDY)‐modified Al current collector affording potassiophilic properties is proposed, which simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…Also, this attractive cycling performance is either comparable to or superior to most previously reported values for K anode stabilized by different strategies in various electrolytes (Figure 4g). [21,22,24,25,31,43,[46][47][48][49][50][51][52][53][54] Importantly, a similar result holds in the EMC-based electrolyte used. The SA-Co@HC/K exhibits superior performance and advanced reaction kinetics than bare K, which further indicates the effectiveness of SA-Co@HC/K composite electrode design in the different electrolytes on the suppression of K dendrites (Figures S26 and S27, Supporting Information).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Also, this attractive cycling performance is either comparable to or superior to most previously reported values for K anode stabilized by different strategies in various electrolytes (Figure 4g). [21,22,24,25,31,43,[46][47][48][49][50][51][52][53][54] Importantly, a similar result holds in the EMC-based electrolyte used. The SA-Co@HC/K exhibits superior performance and advanced reaction kinetics than bare K, which further indicates the effectiveness of SA-Co@HC/K composite electrode design in the different electrolytes on the suppression of K dendrites (Figures S26 and S27, Supporting Information).…”
Section: Resultsmentioning
confidence: 79%
“…[40] Except for the presence of CoN x C species in the SA-Co@HC, the N doping configuration of both HC and SA-Co@HC from the N 1s XPS spectra can be deconvoluted into four nitrogen dopants contributions, including pyridinic-N, pyrrolic-N, graphitic-N, and oxidized-N (Figure 2e and Figure S10, Supporting Information). It was reported that the potassiophilic nitrogen functional sites show large binding energy and stronger adsorption ability for K ion, [29,31,41] which is conducive to regulating the K nucleation and growth property. Overall, all these characterizations confirm the ideal design of envisaged structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2c and Table S1, ESI †). [28][29][30][31][32][33][34][35][36][37][38][39][40] When the current density was 0.1 mA cm À2 , the symmetric battery with 1 M AVIMFSI also cycled for more than 5000 h. The rate performance of symmetric batteries with 1 M AVIMFSI electrolyte is shown in ESI † Fig. S9.…”
Section: Electrochemical Cyclingmentioning
confidence: 99%
“…Compared with traditional carbon materials, GDY has an unparalleled advantage in that it can be grown controllably on the surface of any substrate under low temperatures and mild conditions. Benefiting from these unique properties, a number of GDY-based materials have been fabricated and have shown potential in various fields, including catalysis, energy conversion and storage, batteries, solar cells, intelligence, and life sciences 5,9,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] . These advantages of GDY make it an ideal material for constructing of interface structures with a significant numbers of active sites, facilitated charge transfer, enhanced catalytic activity and longterm stability.…”
mentioning
confidence: 99%